2020
DOI: 10.1017/s0272263120000194
|View full text |Cite
|
Sign up to set email alerts
|

The Aspect Hypothesis and the Acquisition of L2 Past Morphology in the Last 20 years

Abstract: Twenty years ago, a state-of-the-art review in SSLA marked the coming of age of the study of temporality in second language acquisition. This was followed by three monographs on tense and aspect the next year. This article presents a state-of-the-scholarship review of the last 20 years of research addressing the aspect hypothesis (AH) (Andersen, 1991, 2002; Andersen & Shirai, 1994, 1996), the most tested hypothesis in L2 temporality research. The first section of the article gives an overview of the AH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 102 publications
1
38
0
Order By: Relevance
“…(3) Functional theories of SLA emphasize the interplay of form and meaning in acquisition. One much-researched example for morphology is the Aspect Hypothesis (AH) ( Andersen and Shirai, 1996 ; Bardovi-Harlig, 2000 ; for a state-of-the-scholarship review of the last 20 years of research, see Bardovi-Harlig and Comajoan-Colomé, 2020 ). The AH builds on three main constructs: tense, grammatical aspect, and lexical aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Functional theories of SLA emphasize the interplay of form and meaning in acquisition. One much-researched example for morphology is the Aspect Hypothesis (AH) ( Andersen and Shirai, 1996 ; Bardovi-Harlig, 2000 ; for a state-of-the-scholarship review of the last 20 years of research, see Bardovi-Harlig and Comajoan-Colomé, 2020 ). The AH builds on three main constructs: tense, grammatical aspect, and lexical aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, verbal morphology will be attracted to and will occur with predicates with similar semantics. Perfective past will occur with telic predicates (i.e., those with inherent endpoints), imperfective will occur with unbounded predicates, and progressive will occur with ongoing activities” ( Bardovi-Harlig and Comajoan-Colomé, 2020 , p. 3). Bardovi-Harlig and Comajoan-Colomé conclude from their review of perhaps thirty different studies that the AH accurately predicts the adult L2 acquisition of past morphology in a number of languages.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of L2 acquisition of tense-aspect morphology, the prototypical associations, such as achievement verbs, with past tense and activity verbs with the progressive aspect, have been observed and summarized in the Aspect Hypothesis ( Shirai, 1991 ; Andersen and Shirai, 1994 ; Bardovi-Harlig, 2000 ; Bardovi-Harlig and Comajoan-Colomé, 2020 ). It has been suggested that this is because of the compatibility of the semantic representation of lexical and grammatical aspect.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of the L1 factor and the role of inherent aspect has recently been studied by González and Quintana Hernández (2018). To read more about these studies, we refer to González (2019), who shows a current overview of these studies, and Bardovi-Harlig and Comajoan-Colomé (2020), who present a state-of the-scholarship review of the last 20 years of research, in which the most tested hypotheses in L2 temporality research are addressed. Alarcón (2011, p. 332) states that "L2 learners are able to fully develop an implicit grammar of the target language, particularly of L2 grammatical features that are absent in their L1".…”
Section: Tense Aspect and Modality (Tam) In Second Language Acquisitionmentioning
confidence: 99%